PWE-112 The Association of Low Penetrance Genetic Risk Modifiers with Colorectal Cancer in Lynch Syndrome Patients: A Systematic Review and Meta-Analysis. (17th August 2016) - Donald, N; Malik, S; McGuire, J; Monahan, K
Abstract : Introduction: Lynch Syndrome (LS) is a highly penetrant inherited cancer predisposition syndrome accounting for approximately 1000 cases of colorectal cancer (CRC) in the UK annually. LS is characterised by autosomal dominant inheritance and germline mutations in DNA mismatch repair genes. The penetrance is highly variable and the reasons for this have not been fully elucidated. This study investigates whether low penetrance genetic risk factors may result in phenotype modification in LS patients. Methods: A systematic review was conducted of the PubMed and HuGENet databases. Eligibility of studies was determined by pre-defined criteria. Included studies were analysed via the per-allele model and assessed by pooled odds ratios and establishing 95% confidence intervals. Study heterogeneity was assessed via Cochrane's Q statistic and I 2 values. Publication bias was evaluated with funnel plots. Subgroup analysis was conducted on gender. Statistical software used was the Metafor package for the R programme version 3.1.3. Results: Sixty-four polymorphisms were identified and sufficient data was available for analysis of 10 polymorphisms, with between 279 and 1768 CRC cases per polymorphism. None demonstrated association with CRC risk in LS patients. However in sub-group analysis the polymorphism rs16892766 (8q23.3) was significantly associated with CRC risk in males (OR: 1.53, 95% CI: 1.12–2.10). Conclusion: The variable phenotype presentation of the disease still remains largely unexplained, and further investigation is warranted. Other factors may also be influencing the high variability of the disease, such as environmental factors, copy number variants and epigenetic alterations. Investigation into these areas is needed as well as larger and more definitive studies of the polymorphisms analysed in this study. Disclosure of Interest: None Declared